Diagnostic Test Equivalent Hemoglobin Reticulocyte in Iron Deficiency Anemia - Arundina Sanyoto; Ketut Suega; Losen Adnyana; I Made Bakta (The Indonesian Biomedical Journal, 2017)
BACKGROUND: Diagnosing iron deficiency anemia (IDA) is easy, but also can be complicated in condition with inflammation. A new modality for diagnostic which isn’t influenced with inflammation is needed. The aim of this study is to find the cut-off point and evaluate the accuracy of reticulocyte hemoglobin equivalent (Ret-He) to diagnose IDA using ferritin as the gold standard.METHODS: This study was an observational study with cross-sectional analytical design continued with the diagnostic test conducted in anemic individuals with age 18 years old or above.RESULTS: Eighty-seven patients (41 men and 46 women) were included in this study with mean of hemoglobin 7.42 g/dL, serum iron 42.71 mg/dL, total iron-binding capacity (TIBC) 242.82 mg/dL, ferritin 799 ug/L and Ret-He 23.63 pg. Ret-He with cut-off value 25 pg showed a sensitivity 97.2% (95% CI 83.79-99.85%), specificity 66.67% (95% CI 51.97-78.85%), positive predictive value 67.30% (95% CI 52.77-79.28%) and negative predictive value 97.14% (95% CI 83.38-99.85%).CONCLUSION: Ret-He showed the best sensitivity for detection of IDA and was suggested as the screening test for IDA.KEYWORDS: IDA, Ret-He, diagnostic test